PROMOTION MIX TRAINING AS A PREPARATION OF BAMBOO HANDICRAFT EDUCATIONAL TOUR LAUNCHING FOR UMKM AT SUMBERREJO DISTRICT, BOJONEGORO, EAST JAVA - Maurisia Putri Permatasari; Annysa Endriastuti (Darmabakti Cendekia: Journal of Community Service and Engagements, 2020)
Background: This community service is a follow up of community service in Kecamatan Sumberrejo in 2017 and is expected to be the first step to preparing the launching of the bamboo tourism village in Kecamatan Sumberrejo. Purpose: This community service aims to provide solutions for problems faced by partners, preparation for launching and planning the right promotional mix to attract consumers’ interest in the newly formed educational tourism in Kecamatan Sumberrejo. Method: Assistance by the team to partners through counseling, training, and practical assistance. In addition, worksheets have been provided to monitor partner activities and measure the effectiveness of the training. Result: The pre-test and post-test results illustrate an increase in partner knowledge regarding the promotion mix. Conclusion: The material delivered by the team was able to be well understood by partners and partners’ knowledge and interest in marketing through the promotion mix increased.